2013
DOI: 10.1038/ejhg.2013.101
|View full text |Cite
|
Sign up to set email alerts
|

Smaller and larger deletions of the Williams Beuren syndrome region implicate genes involved in mild facial phenotype, epilepsy and autistic traits

Abstract: syndrome (WBS) is a multisystemic disorder caused by a hemizygous deletion of 1.5 Mb on chromosome 7q11.23 spanning 28 genes. A few patients with larger and smaller WBS deletion have been reported. They show clinical features that vary between isolated SVAS to the full spectrum of WBS phenotype, associated with epilepsy or autism spectrum behavior. Here we describe four patients with atypical WBS 7q11.23 deletions. Two carry B3.5 Mb larger deletion towards the telomere that includes Huntingtin-interacting prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 34 publications
(40 reference statements)
1
63
1
Order By: Relevance
“…In WBS itself, most contiguous gene deletions comprise ~1.5 megabase pairs (Mbp) that do not include WBSCR16 (Schubert, 2009). However, WBSCR16 , and a set of adjacent genes, are included in some larger and atypical deletions [(Fusco et al, 2014; Schubert, 2009) and unpublished data]. Efforts are underway to determine phenotypic differences in WBS patients in which WBSCR16 has or has not been deleted.…”
Section: Discussionmentioning
confidence: 99%
“…In WBS itself, most contiguous gene deletions comprise ~1.5 megabase pairs (Mbp) that do not include WBSCR16 (Schubert, 2009). However, WBSCR16 , and a set of adjacent genes, are included in some larger and atypical deletions [(Fusco et al, 2014; Schubert, 2009) and unpublished data]. Efforts are underway to determine phenotypic differences in WBS patients in which WBSCR16 has or has not been deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Three genes-MAGI2 (MIM: 606382), HIP1 (MIM: 601767), and YWHAGhave been suggested as possible candidates for these atypical features. [46][47][48][49][50][51][52][53] Ramocki et al 51 suggested that haploinsufficiency of HIP1 is sufficient to alter neuronal homeostasis and cause focal and generalized epilepsies and cognitive dysfunction. However, their findings do not exclude the possibility that YWHAG loss of function is sufficient to cause neurological phenotypes alone, as proven by our results.…”
mentioning
confidence: 99%
“…Also studies in WS have underlined the importance of genotype-phenotype correlation. For instance, Fusco and colleagues suggested that larger deletions extending distally in individuals with WS give more severe developmental delay and ID [76]. Moreover, hemizygosity of LIMK1, CLIP 2, GTF2IRD1 and GTF2I is generally associated with a better cognitive profile in WS [77,78].…”
Section: Discussionmentioning
confidence: 99%